Influence of long-term administration of non-steroidal antiinflammatory drugs on the level of whole genome DNA methylation and its fragmentation in rats - Burlakа, K. A.; Бурлака, Кристина Анатоліївна (My University, 2023)
In recent years, there has been rapid growth in epigenetic research associated with the development of new molecular and cytological approaches. Recent studies have established that chemical compounds can have an epigenetic effect, influencing the expression activity of specific genes. And most often, it is connected with people with chronic diseases because they are forced to use medicines for a long time to improve their quality of life. It is known that long-term use of non-steroidal anti-inflammatory drugs (NSAIDs) leads to the formation of erosions, ulcers and oncological diseases of the stomach and intestines. It is suggested that side effects result from damage to the mucous membrane under the influence of NSAIDs and the possible effect of NSAIDs on genes that regulate the cell cycle, especially with their long-term use. In the research, 60 male rats were used, which were divided into four groups of 15 animals each, which were administered NSAIDs daily for 3 months: 1st – control (CG), 0.9% sodium chloride solution, 2nd – rats , which were injected with indomethacin, the 3rd group – rats, which were injected with acetylsalicylic acid, and the 4th group – rats, which were injected with meloxicam. Long-term use of all NSAIDs led to a statistically significant increase in genome-wide DNA methylation and intensification of its fragmentation processes. It is important to note that according to the degree of epigenetic influence, the effect of the studied NSAIDs was of varying severity. Indomethacin had the most pronounced effects (increase of MspI/HpaII by 99%; DNA fragmentation by 90% compared to intact). Taking into account the established effects of NSAIDs, regarding their ability to increase the level of whole-genome DNA methylation and their fragmentation, a promising direction is to study the level of methylation of genes that regulate the cell cycle of the stomach and intestines, as well as the study of their expression/protein synthesis function. За останні роки, спостерігається бурхливе зростання епігенетичних досліджень, пов'язаних з розвитком нових молекулярних і цитологічних підходів. Останніми дослідженнями було встановлено, що хімічні сполуки можуть мати епігенетичний вплив, тобто впливати на активність експресії певних генів. А найчастіше, це пов’язано з людьми які мають хронічні захворювання, тому що вони вимушені застосовувати лікарські засоби тривало, з метою покращення якості життя. Відомо, що тривалий прийом нестероїдних протизапальних лікарських засобів (НПЗЗ) приводить до утворення ерозій, виразок і онкологічних захворювань шлунка та кишечника. Висловлюється припущення, що побічні ефекти є не тільки результатом пошкодження слизової оболонки під впливом НПЗЗ, але і можливим впливом НПЗЗ на гени, які регулюють клітинний цикл, особливо при їх тривалому застосуванні. У дослідженнях були використані 60 щурів-самців, які були розподілені на чотири групи по 15 тварин, котрим вводили щоденно у продовж 3 місяців НПЗЗ: 1-а – контрольна (КГ), розчин натрію хлориду 0,9%, 2-га – щури, котрим вводили індометацин, 3-я – щури, котрим вводили ацетилсаліцилову кислоту та 4-а група – щури, котрим вводили мелоксикам. Тривале призначення всіх НПЗЗ призводило до статистично вірогідного збільшення повногеномного метилювання ДНК та до інтенсифікації процесів її фрагментації. Важливо зазначити, що за ступенем епігенетичного впливу, дія досліджуваних НПЗЗ була різного ступеня вираженості. Найбільш вираженими ефектами володів індометацин (збільшення MspI/HpaII на 99 %; фрагментації ДНК – на 90% по відношенню до інтакту). Враховуючи встановлені ефекти НПЗЗ, щодо їх здатності підвищувати рівень повногеномного метилювання ДНК та їх фрагментації, перспективним напрямом є вивчення рівня метилювання генів, що регулюють клітинний цикл шлунка та кишечника, а також вивчення їх експресивної/білоксинтетуючої функції.
Вплив тривалого введення нестероїдних протизапальних засобів на рівень повногеномного метилювання ДНК та її фрагментації у щурів
Keywords: DNA methylation; epigenetics; ulcerogenic effect; non-steroidal anti-inflammatory drugs; метилювання ДНК; епігенетика; ульцерогенна дія; нестероїдні протизапальні лікарські засоби